Motivation and employee satisfaction in the Niceboy company - Vojtíšek, Anna Marie; Křečková Kroupová, Zuzana, 1972-; Kloudová Jiřičková, Václava; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This bachelor thesis focuses on the levels of motivation and employee satisfaction in the Czech company Niceboy. The aim of this thesis is to critically assess the motivation and satisfaction of employees when compared with the expectations of management in the Niceboy company. Outcomes will be assessed along with the recent business trends. Firstly, the theoretical part focuses on motivation and explains it from different angles, while also overviewing various motivation theories. The thesis also deals with job satisfaction and its relation to both performance and motivation, as well as dedicating a chapter to communication in companies. Next, the practical part introduces the Niceboy company and by use of different research methods analyses the current motivation and satisfaction system set in the company and its perception by employees. Lastly, the conclusion offers recommendations to the company on how to deal with the strengths and weaknesses of the motivational system brought up by the research and what to focus on in the future.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses